KAPASITAS PEMERINTAHAN DESA DALAM MENGHADAPI IMPLEMENTASI UNDANG-UNDANG NO. 6 TAHUN 2014 TENTANG DESA (di Pemerintahan Desa Tutul, Desa Balung Kulon, dan Desa Balung Lor Kecamatan Balung Kabupaten Jember) - Zakia Zakia; Irfan Ridwan Maksum (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2017)
This research is analyzing about the capacity of rural government and the capacity building strategy in facing the implementation of Act No. 6 of 2014 about village. The research held in three rural governments they are Tutul, Balung Kulon and Balung Lor Sub-district Balung District Jember. This research is using qualitative method with descriptive design. The result of the study suggest that the authority of the village should be reinforced to solve governance related problems, it also needs to review the coaching program because the schemes tend to be elitist along this time, so it does not really fit to the rural government official’s necessary; furthermore, the stakeholders of rural government (local governments) should be involved to help strengthen the capacity of rural government both in terms of policies, resources or technical assistance. In addition, it also needs to involve the universities and non-governmental organizations in order to open and expand the new discourse about the renewal of the village